Pension certificate of Parker C. Thomas - Thomas, Parker C.
Certificate from the Dept. of Interior granting Thomas a pension for his Civil War service.
Soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Department of the Interior; Military pensions -- United States -- Civil War, 1861-1865.; Soldiers